Evolutionary Multi-Criterion Optimization 5th International Conference, EMO 2009, Nantes, France, April 7-10, 2009, Proceedings - Fonseca, Carlos M.; Gandibleux, Xavier; Hao, Jin-Kao; Sevaux, Marc (Theoretical Computer Science and General Issues, 2009)
This book constitutes the refereed proceedings of the 5th International Conference on Evolutionary Multi-Criterion Optimization, EMO 2009, held in Nantes, France in April 2009. The 39 revised full papers presented together with 5 invited talks were carefully reviewed and selected from 72 submissions. The papers are organized in topical sections on theoretical analysis, uncertainty and noise, algorithm development, performance analysis and comparison, applications, MCDM Track, Many objectives, alternative methods, as well as EMO and MCDA.